Social Media Portfolio: Zazzy Wardrobe / Hazimahtun Hasyimah Md Shariff - Md Shariff, Hazimahtun Hasyimah (2021)
Zazzy Wardrobe is a sole proprietorship type of business that was established on 1st October 2020 by Hazimahtun Hasyimah Binti Md Shariff. The company is located at Jalan Kluang-Jemaluang, Taman Sam Hoe, Kampung Gunung Lambak, Kluang, Johor, 86000, Malaysia. Three people who work alongside Hazimahtun are Nurul Syuhada Binti Roslan as Administrative Manager, Nurul Syafiqah binti Saher as Financial Manager, and Zulaikha Nadia binti Mohd Hashim as Marketing Manager. Each of us has the background and qualification in entrepreneurship and business which enables us to share the knowledge and contribute it to the business flow and progress. Zazzy Wardrobe is a celebration of effortless feminine allure. The label provides women with timeless wardrobe essentials – from chic yet comfortable basics to intricate a lifestyle brand for the modern city girl and occasion wear. Playful, yet classy. Stylish, yet friendly. Urban chic and cool. These characteristics have become hallmarks of the company. High-quality materials at an affordable price, Zazzy Wardrobe prides itself in creating loyal customers by providing a high level of comfort for the dresser. With its unswerving focus on quality and attention to detail, Zazzy Wardrobe provides the everywoman a piece of wearable history – at the heart of each collection is a charismatic mosaic of personal stories. At Zazzy Wardrobe, we believe in the power of telling stories and of course, in wearing them.